Community Service Contributions: Impact on the English Club’s Growth - The, Hery Yanto (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study aims to describe the activities and outcomes of the English Club at SMA G after one year, using a qualitative case study approach to examine the program's impact on students' language learning. The researcher facilitated the club's activities and served as a mentor. Through discussions with the school's English teachers, counselors, and vice principals, club activities were developed to meet student interests and language levels. Data collection involved observations, lesson plans, attendance records, formative assessments, and photovoice, a method allowing students to capture and reflect on their experiences visually. During the year, the program had 15 sessions, and the average student attendance rate was 74.03 percent out of 32 and 24 students, respectively, for the first and second semesters. Although some students had scheduling conflicts because of academic obligations, those who attended showed strong motivation, especially for conversational practice. The findings suggest that speaking skills have improved significantly, particularly among lower-proficiency students who have gained confidence and vocabulary fluency. The analysis of photovoice revealed high levels of social engagement and collaboration, which reinforces the importance of interactive, supportive environments in language development. This study emphasizes the significance of structured extracurricular programs in improving student language abilities and presents a framework for integrating similar community-supported initiatives in educational settings. The findings suggest that programs such as the English Club can be essential in fostering language acquisition and student engagement.